Intergenerational mobility and the rise and fall of inequality: Lessons from Latin America - Guido Neidhöfer (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
Countries with high income inequality also show a strong association between parents' and children's economic well-being; i.e. low intergenerational mobility. This study is the first to test this relationship in a between and within country setup, using harmonized micro data from 18 Latin American countries spanning multiple cohorts. It is shown that experiencing higher inequality in childhood has a negative effect on intergenerational mobility as adults. Furthermore, the influence of economic growth and public education is evaluated: both have a positive, significant, and substantial effect on intergenerational mobility.
Keywords: D63; I24; J62; O15; 330; Inequality; Intergenerational Mobility; Equality of Opportunity; Human Capital; Growth; Development; Public Education; Great Gatsby Curve; Latin America